2019
DOI: 10.18203/2394-6040.ijcmph20194466
|View full text |Cite
|
Sign up to set email alerts
|

Association between behavioural, metabolic risk factors of non-communicable diseases and socio-demographic factors among Bihari population in Bangladesh

Abstract: Background: The Bihari community is an underprivileged group of people, immigrants from Pakistan during 1971 independence war, now living in Bangladesh. This community is considered as vulnerable for not having adequate health care facilities and access to health services. The current study is aimed to determine the association between behavioural, metabolic risk factors of non-communicable diseases (NCD) and socio-demographic factors among Bihari community in Bangladesh.Methods: It was a community based cross… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…only 42% of respondents were found using normal level of salt per day. A study by Ahmed et al 12 showed half (52.5%) were used to take added salt during their meal.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…only 42% of respondents were found using normal level of salt per day. A study by Ahmed et al 12 showed half (52.5%) were used to take added salt during their meal.…”
Section: Resultsmentioning
confidence: 99%
“…In south Asia Bangladesh is a lower middle income country with a population of over 160 million in 2015; while infectious diseases are still prevalent, the burden of NCDs is also increasing, even among the poor [10][11][12][13][14][15][16][17][18] . Population-based NCD risk factor surveys using a standardised method from the WHO called the STEP wise approach to surveillance (STEPS) 11 had been conducted four times in the past in Bangladesh.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation